Effects of a complex semi-natural cage system on Sprague Dawley rat welfare using behaviour, faecal glucocorticoid metabolites and selected organ weights as indicators - Naidoo, Vinny (University of Pretoria, 2023)
Mini Dissertation (MMedVet (Laboratory Animal Science))--University of Pretoria, 2023.